2014
DOI: 10.1089/jwh.2014.4736
|View full text |Cite
|
Sign up to set email alerts
|

Women's Participation in the Medical Profession: Insights from Experiences in Japan, Scandinavia, Russia, and Eastern Europe

Abstract: Although much literature has focused on the status of female physicians in the United States, limited Englishlanguage studies have examined the role of women in the medical profession elsewhere in the world. This article synthesizes evidence regarding the status of female physicians in three purposively selected regions outside the United States: Japan, Scandinavia, and Russia and Eastern Europe. These three regions markedly differ in the proportion of female physicians in the workforce, overall status of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
82
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 42 publications
2
82
0
7
Order By: Relevance
“…Approximately equal numbers of women and men enter and graduate from medical school in the United States and United Kingdom. 1 2 In northern and eastern European countries such as Russia, Finland, Hungary, and Serbia, women account for more than 50% of the active physicians 3 ; in the United Kingdom and United States, they represent 47% and 33% respectively. 4 5 Even in Japan, the nation in the Organisation for Economic Co-operation and Development with the lowest percentage of female physicians, representation doubled between 1986 and 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately equal numbers of women and men enter and graduate from medical school in the United States and United Kingdom. 1 2 In northern and eastern European countries such as Russia, Finland, Hungary, and Serbia, women account for more than 50% of the active physicians 3 ; in the United Kingdom and United States, they represent 47% and 33% respectively. 4 5 Even in Japan, the nation in the Organisation for Economic Co-operation and Development with the lowest percentage of female physicians, representation doubled between 1986 and 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Another theme identified across various countries is that despite the increasing proportion of women in medicine, their careers progress much more slowly than their male colleagues (e.g., in gaining permanent positions, significant representation in hierarchical medical positions, etc.) [13, 22–24]. A related but slightly different perspective on this theme comes from a study in Scotland, which found that women primary care providers tend to work fewer hours and are less likely to engage in teaching and administrative duties than their male colleagues, suggesting important implications for countries’ physician workforces [25].…”
Section: Introductionmentioning
confidence: 99%
“…Medicine is an especially relevant discipline for researching the problem, as the field remains characterised by both horizontal and vertical discrimination [6][7][8] and because it is considered a traditionally "masculine" institution [9] despite the increase in female medicine students around the world [10,11]. Furthermore, for a long time, a habilitation was considered proof of scientific qualification in lieu of a doctorate, which is awarded to all graduates of medical studies.…”
Section: Introductionmentioning
confidence: 99%